2009
DOI: 10.1021/jp811516s
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Dipole Approximation Calculations of Optical Properties of Silver Nanorod Arrays in Porous Anodic Alumina

Abstract: The experimental extinction spectrum of 38 nm long silver nanorods grown in the 22 nm pores of an anodic aluminum oxide (AAO) template is theoretically analyzed, using the discrete dipole approximation (DDA) method. A single broadband at 485 nm in the spectrum turns out to be the overlap of the two peaks at 430 and 515 nm, corresponding to the transverse and longitudinal modes of the surface plasmon of the nanorods, respectively, at small angles e75°of incidence. Interestingly, the longitudinal mode in the arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…The average diameter and length of GNRs are 25 nm and 55 nm, respectively. Based on these data and discrete dipole approximation (DDA) calculation method (Kim et al, 2009), the simulated extinction spectrum of our synthesized GNRs could also be obtained (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The average diameter and length of GNRs are 25 nm and 55 nm, respectively. Based on these data and discrete dipole approximation (DDA) calculation method (Kim et al, 2009), the simulated extinction spectrum of our synthesized GNRs could also be obtained (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many studies have been focused in the optical properties of non-spherical metal nanoparticle arrays, such as nanorods [27], nanodisks [28], nanowires [29]. Yin et al reported the SPR peak shift of a one-dimensional silver cylinder array with different interparticle distances [30].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the angular dependence of near-field enhancement was also found in the vertical AgNR arrays. It has been revealed that different modes of surface plasmon resonance can only be excited by certain angles of incidence, leading to different near-field enhancements [23,33]. Figure 9a shows the polarization dependence of EF avg from S42 AgNR hexagonal array with AR = 3.5.…”
Section: Effect Of Incident Anglementioning
confidence: 99%